A Dosimetric Evaluation of Thyroid Sparing and Thyroid Optimised Radiotherapy in Locally Advanced Head and Neck Cancer - Vydia, Gautam Vedagiri; Ranganathan, Arulpandiyan; Kaluvoya, Ramanaiah; S, Sadanand; B, Mukesh; Perumal, Sundaravadhana; M N, Arun Kumar (Asian Pacific Journal of Cancer Care, 2025)
Background: Radiation-induced hypothyroidism is a frequent complication of radiotherapy for head and neck cancers due to the thyroid’s proximity to treatment areas. Advances in radiation therapy, such as Intensity Modulated Radiation Therapy (IMRT), have made it possible to reduce radiation exposure to the thyroid while maintaining effective tumor coverage. This study evaluates the dosimetric outcomes of thyroid-optimized (TO-IMRT) and thyroid-sparing (TS-IMRT) techniques in reducing thyroid radiation dose without compromising treatment efficacy. Methods: A retrospective analysis was conducted on 10 patients with oral cavity and oropharyngeal cancers treated with IMRT between 2020 and 2023. Three treatment plans were compared for each patient: thyroid-non-optimized (TNO-IMRT), TO-IMRT, and TS-IMRT. Dosimetric parameters including mean thyroid dose, dose-volume coverage (V100%, V95%), and target coverage were analyzed across the three plans. Statistical significance was evaluated using paired t-tests, with a p-value < 0.05 considered significant. Results: Both TO-IMRT and TS-IMRT significantly reduced the mean thyroid dose compared to TNO-IMRT. The mean thyroid dose in TNO-IMRT ranged from 4951 to 5890 cGy, whereas TO-IMRT reduced it by an average of 12–15%, and TS-IMRT by up to 20–25%. PTV coverage was maintained across all plans, with V100% and V95% showing minimal reductions. For example, in PT1, V100% was 91.5% in TNO-IMRT, 90.6% in TO-IMRT, and 91.0% in TS-IMRT. Similar patterns were observed across all patients. Conclusion: Thyroid-optimized and thyroid-sparing IMRT techniques effectively reduced thyroid radiation dose without compromising target volume coverage in head and neck cancer patients. The significant dose reduction observed with TS-IMRT suggests a promising approach to mitigating radiation-induced hypothyroidism, enhancing patient outcomes and long-term quality of life. Further studies with larger cohorts are recommended to confirm these findings.